PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID -19 DI SMP ISLAM MBAH BOLONG WATUHGALUH JOMBANG - yudi, Wahyu; Nisa', Khoirun (STAI Ma'had Aly Al-Hikam Malang, 2021)
Covid-19 has an effect in every area of people's life, one sector is education. Education in Indonesia seems to be getting a shock that creates a new order in the learning process. So as to make the distance learning process, it must be implemented considering the Ministry of Education and Culture's instructions to continue learning amid the Covid-19 outbreak. Teachers are required to make learning plans related to Distance Learning, which has never been implemented before. From the limitations of PAI teachers at the junior high school level who are accustomed to face-to-face learning, they must make distance learning. Teachers at SMP Islam Mbah Bolong Watugaluh Jombang as research respondents turned out to have advantages in preparing for the learning process during the Covid-19 period. In Distance Learning they are able to continue working by optimizing all the potential that exists through electronic media. difficulties and ease in implementing distance learning cannot be avoided. This is also an attraction for research related to the distance learning process at Mbah Bolong Watugaluh Islamic Junior High School in Jombang.